Local communities of the Bothnian Arc in a prehistoric world - Hakonen, A. (Aki) (Oulun yliopisto, 2021)
Abstract The aim of this study is ultimately to expand our understanding of the prehistoric world closer to the individual. The focus is on the Bothnian Arc and its local communities lost in time. To understand them, we need to understand the wider Central Fennoscandian prehistory. The main timeframe is 5500 BCE to 600 CE. The study applies, among other methods, 3D topographical analyses on archival and digital materials. The theoretical framework is formed around Latourian Actor-Network Theory and Modes of Existence, and the anthropological economic theory of the late David Graeber. The purpose of the theoretical assemblage is to gain a perspective beyond the modern Western notions of society and economy. Accordingly, the geography of Central Fennoscandia can be populated with non-human agencies and entities, who would not have gone unnoticed from the local inhabitants. Most notably, post-glacial land uplift animates the geography, while also providing local archaeology with the tool of shoreline displacement chronology. The narrative of the prehistory of Central Fennoscandia indicates that after agrarian forms of subsistence began to expand into the region during the 4th and 3rd millennia BCE, a constantly shifting frontier between agricultural and forager contexts persisted in the region for over four millennia. Regarding the politics of these communities, it is argued that the different modes of subsistence were ingrained in ideology. Subsistence ideology affected attitudes to labor and organization. This approach highlights the cultural division within the region. Analyzing mortuary practices as signs of respect and morality alleviates the division, while shifting the contrast to highlight the divergence between the multivalence of prehistoric mortuary practices and the singularism of Christian dogma. This multivalence is further investigated by a comparative study of the material records of two regions within the Bothnian Arc. The results indicate that the local communal identities differed from each other ...